'Keeping news alive in Venezuela': Using social media as tactical media. (April 2023) - Pain, Paromita; Korin, Ezequiel
Venezuela leads Latin America with the largest number of imprisoned journalists and extreme government-led media censorship. Our in-depth interviews with 25 Venezuelan journalists reveal that assisting journalists to combat government control are social media and technology platforms like WhatsApp, Facebook and Twitter, which, in Venezuela, have moved beyond their ability to share and mobilise, and have become tactical media, the media of crisis criticism and opposition.